HUBUNGAN OKSIDA NITRAT DAN NILAI HISTOPATOLOGIS PADA ENDOTOKSEMIA - Sotianingsih, Sotianingsih; Suharyo, Suharyo; S, Lisyani; HA, Guntur (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Lipopolysaccharide (LPS) is an endotoxin from the outer membrane of Gram-negative bacteria, which has an important role in the occurrence of sepsis. Exposure to LPS will stimulate increase of nitric oxide (NO). Nitric oxide is a bioregulator of apoptosis and has some sepsis prognostic role of apoptosis regulators within the gastrointestinal cells. The objective of the study is to know if endotoxemia induces an increase in NO levels and histopathology scores as well as the existing relationship between them. This study is an observational intervention. The subjects were 48 male mice Balb/C, divided into 2 groups. The samples consisted of 24 tail as control group (group A) and 24 as treatment group (group B). The A group as well as the B group is divided into 4 subgroups according to the time of termination. The levels of NO were examined by Griess method. Histopathology score was examined by HE and read as a score of 0–5. There was a statistically significant difference between the mean NO in the treatment group with the control group at the termination of the group of 12h (p=0.009), 24h (p=0.015), 36h (p=0.014), 48h (p=0.002) and the whole group (p=0.0001), as well as between the mean histopathology score at the termination time of 12 h (p=0.0001), 24h (p=0.0001), 36h (p=0.0001), 48h (p=0465) and the whole group (p=0.0001). Increase in NO and histopathology scores in all groups of mice (r=0.527) showed a statistically significant correlation. NO levels and histopathology scores are increased during endotoxemia and thus have a significant correlation.